PERMAINAN TRADISIONALMAJARAN-JARANAN DAN MAKERING ENDUT SEBAGAI PENDIDIKAN KARAKTER: NILAI LUHUR DALAM TRADISI LISAN DESA BANYUNING SINGARAJA - Puteri Yadnya Diari; Luh Ketut Suciarini (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2020)
Oral tradition According to Hoed (2008: 184) is a variety of knowledge and customs that have been passed down from generation to generation orally. Hoed's affirmation has a close relationship with the definition of oral tradition conveyed by Albert Lord, both of which focus on the hereditary process of using orality as the medium. Lord defines oral tradition as something that is spoken in society. The speaker does not write down what he says but speaks it, and the recipient does not read it, but hears (1995: 1). One of the forms of the oral tradition is the traditional games of majaran-jaranan and makering endut in Banyuning Singaraja Village. It contains four meanings as a medium for character formation including a) meaning related to religious elements; b) meaning related to human beings; c) meaning related to the service of the State / love for the country; d) meaning related to human personality. This study is qualitative approach with ethnographic methods was used to express and understand the learning of the values contained in the traditional games of majaran-jaranan and makering endut.Keyword: Traditional game, Character Education, Oral Traditon